Land use changes by mesoregion in Slovenia between 2000-2022 - Žiberna, Igor; Ivajnšič, Danijel (Journal for Geography, 2022)
Land use changes by mesoregion in Slovenia between 2000-2022The artcle shows changes in land use by mesoregions in Slovenia. Changes are analysed according to elelven catagories of land use: fileds and gardens, vineyards, orchards, other permanent crops, meadows, land in overgrowth, mixed land use, forest, built-up and related areas, oher areas, water bodies. The directions of land use change are also discussed, with special regard to changes from cultivated to non-cultivated areas and vice versa. Based on this, the extensification coefficients were calculated. Land-use changes in areas of strategic importance for agricultur and food production are also analysed.
Keywords: Abandonment of arable land; land use; mesoregions; Slovenia